Mortality in males treated for an eating disorder—A large prospective study. Issue 12 (10th July 2019) - Quadflieg, Norbert; Strobel, Christine; Naab, Silke; Voderholzer, Ulrich; Fichter, Manfred M.
Abstract: Objective: To report on the long‐term mortality of eating disorders in male inpatients. Method: Crude mortality rates (CMR) and standardized mortality ratios (SMR) were computed for a large sample of males (147 anorexia nervosa [AN], 81 bulimia nervosa [BN], 110 eating disorder not otherwise specified [ED‐NOS]; DSM‐IV). In addition, a survival analysis from onset of eating disorder to death or end of observation was computed. Results: CMR was 12.9% in AN, 11.1% in BN, and 6.4% in ED‐NOS. Standardized mortality was significantly elevated in males with AN (SMR = 5.91; 95% confidence interval 3.56–9.23) as well as ED‐NOS (SMR = 3.40; 95% confidence interval 1.37–7.01) but not in males with BN (SMR = 1.88; 95% confidence interval 0.86–3.58). Males with AN died sooner after onset of eating disorder than males with BN or ED‐NOS. Discussion: Mortality in male inpatients with eating disorder is high, especially in AN. There is need for developing more effective treatments to achieve better outcome.